Wpływ Ujemnej Krzywizny Wykresu σ = σ(ε) na Parametry Fali Naprężenia w Gruncie - Włodarczyk, E. (Engineering Transactions, 1971)
In this paper, a closed analytical solution is obtained for the wave problem of the unloading of a week discontinuity propagated in the friable, dry ground, approximated by a curvilinear characteristic σ = σ(ε) with a negative curvature (d^2 σ/de^2